Addition of organic and inorganic amendments to regenerate the surface structure of silty soils - Gabioud, Emmanuel Adrian (2019)
The widespread degradation of the structure of silty soils under no till systems (NT) that has been observed in recent years is characterized by the presence of a platy structure (P) near the soil surface. Under these conditions, addition of organic and inorganic amendments could have beneficial effects on soil physical properties. We assessed structural regeneration following addition of amendments in an Argiudoll of Paraná, Argentina. Poultry litter (PL) and gypsum (G) were applied, providing an organic and inorganic amendment, respectively. Four treatments were tested: PL (7.5 Mg/ha), G (3 Mg/ha), the combination of PL + G (7.5 + 3 Mg/ha), and control (T) with no amendment. Description and quantification of the structural state of the soil profile was made using a Visual Soil Evaluation method: “Le profil cultural”. Aggregate stability, bulk density, total porosity, pore size distribution and soil shear strength for each soil structure and soil organic carbon (SOC) were determined at two depths. Twenty months after the amendment applications, both PL and PL + G treatments led to a significant increase of SOC in the upper 5 cm of soil. The proportion of Gamma (Γ) structure increased and P declined under PL and PL + G compared with G and T inn the A horizon. Treatments G and PL + G contributed to an increase in average diameter of aggregates in Γ only. The use of PL amendment alone or in combination with G could be a promising strategy to regenerate, in the short‐term, the degraded soil structure under NT.